Optimization of Quadruple Helix Using RUMEUNG App for Sustainable Tourism Development in West Java - Nur Hendrasto, Sutopo, Elang Ilik Martawijaya, Abdullah Haidar (Journal of Sustainable Economics, 2024)
The development of tourism concepts requires collaborative efforts across multiple stakeholders. This study focuses on enhancing the tourism sector through the "RUMEUNG" application, designed to integrate efforts from government, academia, business, and local communities. Such integration is essential for fostering creativity, ensuring high-quality final products, and maintaining competitiveness in the increasingly diverse market of tourism. West Java, an expansive region, is identified as having 2,583 potential tourist sites as per the Department of Tourism and Culture. To optimize these assets, coordinated development and marketing strategies are critical. This qualitative study uses descriptive research techniques to assess and improve the usability of the "RUMEUNG" application’s user interface. It adopts the Lean UX methodology for design and evaluates the outcomes using Single Ease Questions (SEQ) and the System Usability Scale (SUS). Additionally, the research explores the application of the Quadruple Helix model in tourism development in West Java through the RUMEUNG program, aiming to enhance digital integration among the key stakeholders. Results indicate that the user interface design of RUMEUNG is highly accessible, with a SEQ score of 8.5%. Most users found the interface to be extremely easy to use (7%), while others rated it as easy (12%) and very easy (3%). The SUS scores were also favorable, falling within the grade B range (80-90), which reflects good usability. By implementing a Quadruple Helix approach, the RUMEUNG application potentially facilitates robust collaboration, promoting sustainable tourism development in West Java.